Effects of ethyl methanesulfonate on growth and yield parameters of wheat and tolerance to imazamox - Bayhan, Merve; Özkan, Remzi; Albayrak, Önder; Akinci, Cuma; Yildirim, Mehmet (Bangladesh Journal of Botany, 2024)
In the present study objective bread wheat (Triticum aestivum L.) and durum wheat (Triticum durum Desf.) lines resistant to Imazamox herbicides and effective lethal ethyl methanesulfonate (EMS) doses for plants. During first year (2019/2020), 1000 seeds of bread wheat and durum wheat treated with 11 different EMS doses were sown under field and greenhouse conditions. During second year (2020/2021), M1 (first generation) cereal seeds were grown as M2 (second generation) in field experiments. Herbicide with Imazamox active ingredient at 125 ml da-1 was applied to the approximately 15 cm tall plants in the M2 generation. In bread and durum wheat lines, emergent plants were observed up to a dose of 60mM EMS. The effective EMS doses for the wheat species were determined as 80 mM for bread wheat and 50 mM for durum wheat. Bangladesh J. Bot. 53(3): 487-493, 2024 (September)